Pengaruh Media Terasio Terhadap Kemampuan Keterampilan Menulis Teks Laporan Hasil Observasi Kelas VIII - Alfiani Salsabila; Khaerunnisa Khaerunnisa (Universitas Muhammadiyah Jember, 2025)
Education plays a central role in forming an intelligent and competitive generation. One important component in the learning process is learning media, which functions to support student involvement in absorbing material effectively. This study aims to determine the effect of using Terasio learning media on the writing skills of observation report texts of class VIII students at SMP YAPIA Pondok Aren. Terasio media is a website-based media with a birdcage design designed to support interactive and collaborative learning. The research method used is an experiment with a posttest-only control design, involving two groups, namely the experimental group that received treatment and the control group that did not receive treatment. The sample consisted of 54 students who were selected randomly. Data collection techniques include observation, interviews, tests, and documentation, with data analysis through normality tests, homogeneity tests, and t-tests. The results showed that students in the experimental class obtained higher learning outcomes compared to the control class. The significant value of the t-test of 0.000 <0.05 proves that there is a significant effect of using Terasio media on improving the writing skills of observation report texts. The conclusion of this study is that Terasio media is able to increase students' motivation, activeness, and critical thinking skills in writing, as well as making the learning process more enjoyable and meaningful.